Dedicated : the case for commitment in an age of infinite browsing - Davis, Pete, 1989- (Avid Reader Press, 2021)
In a culture of restlessness and indecision, which causes tension in people's lives, a civic advocate, using examples from history, personal stories, and applied psychology, shows how purposeful commitment can be a powerful force.